Virtual Exploration and Annotation of EPAD1 gene in Poaceae - Bibi, Sadia; Noor, Wajia; Gul, Safia; Jamshid, Nida; Jabbar, Sadia; Ahmad, Mushtaq (Journal of Agriculture and Biology, 2025)
Pollen grain is enclosed in the multi layered cell wall, combating chemical, physical and other stress conditions. The wall sculpturing of the pollen imparts substantial taxonomical evidence for the classification. This characteristic configuration is comprised by the accumulation of sporopollenin on the template primexine. Recently identified EPAD1 (Pollen Exine Pattern Designer) gene discovered to be responsible for the ornamentation of pollen wall. This research is aimed at the investigation of EPAD1 gene, confirmation of EPAD1 role in pollen wall sculpturing through virtual screening. EPAD1 gene homologs are determined in Poaceae, along with gene annotation, protein virtual modelling, conservation analysis, phylogenetic investigation and functional hits observation, manipulating BLAST, QuickGo, ChimeraX, Weblogo, MUSCLE and ExPasy-PROSITE respectively. Twenty-six homologs are investigated with highest identity 93% and query coverage 63% in Oryza meyeriana. EPAD1 annotation revealed that it performs in the pollen wall assembly, development, external encapsulating structure, gametophyte development, anatomical structures and morphogenesis. Orn/DAP/Arg decarboxylases family 2 structure 2 and twin arginine translocation (Tat) signals profile hits are observed on predicted homologs of Poaceae. The determined hits on EPAD1 functional analysis confirmed its inclusion in designing pollen morphology. The amino acids in the selected query coverage expressed high conservation for EPAD1 among grasses. Similarly, the phylogenetic evaluation represented the comparative relation and evolutionary patterns among the homolog species at genus level. Divergent species of the same genus Triticum, Oryza, Panicum and Setaria conjoint the corresponding note in phylogeny with the other species of similar genus. Briefly gene for pollen exine designing requisite to be investigated in other plant families, as it was discovered to be family specific. These outcomes will accelerate exploration of exine ornamentation and comparative plant families essay, based on the pollen exine designer gene.
Keywords: Pollen; Exine; sporopollenin; ornamentation; gene; homology; ontology; Poaceae